Big-conductance Ca2+-activated K+ channels in physiological and pathophysiological urinary bladder smooth muscle cells. Issue 5 (2nd September 2016) - Parajuli, Shankar P.; Zheng, Yun-Min; Levin, Robert; Wang, Yong-Xiao
ABSTRACT: Contraction and relaxation of urinary bladder smooth muscle cells (UBSMCs) represent the important physiological functions of the bladder. Contractile responses in UBSMCs are regulated by a number of ion channels including big-conductance Ca 2+ - activated K + (BK) channels. Great progress has been made in studies of BK channels in UBSMCs. The intent of this review is to summarize recent exciting findings with respect to the functional interactions of BK channels with muscarinic receptors, ryanodine receptors (RyRs) and inositol triphosphate receptors (IP3 Rs) as well as their functional importance under normal and pathophysiological conditions. BK channels are highly expressed in UBSMCs. Activation of muscarinic M3 receptors inhibits the BK channel activity, facilitates opening of voltage-dependent Ca 2+ (CaV ) channels, and thereby enhances excitability and contractility of UBSMCs. Signaling molecules and regulatory mechanisms involving RyRs and IP3 Rs have a significant effect on functions of BK channels and thereby regulate cellular responses in UBSMCs under normal and pathophysiological conditions including overactive bladders. Moreover, BK channels may represent a novel target for the treatment of bladder dysfunctions.